The development of rational number knowledge: Old topic, new insights. (June 2015) - Vamvakoussi, Xenia
Abstract: The development of rational number knowledge has been studied extensively by mathematics education researchers, cognitive-developmental psychologists and, more recently, by neuroscientists as well. Building on a rich body of prior research, and some exciting new ideas, the target articles re-visit several topics, with a view to refine and deepen our understanding of how rational number understanding develops. The effect of prior natural number knowledge-either positive or adverse-on rational number learning is highlighted by all contributors. I draw on the articles to discuss five different aspects of the whole, or natural, number bias. Highlights: There are many reasons why the development of rational number knowledge is challenging for students. A major source of difficulty is the whole/natural number bias. Five different aspects of this bias are discussed. The positive role of prior natural number knowledge is also considered.